Synthesis and characterization of novel hydrazide-hydrazones and the study of their structure-antituberculosis activity - KAYMAKÇIOĞLU, BEDİA (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2006)
A series of hydrazide-hydrazones, based on a series of 4-substituted benzoic acid, were synthesized, and their structures were elucidated and screened for the antituberculosis activity against Mycobacterium tuberculosis H37Rv with the help of the BACTEC 460 radiometric system. Compound 3. 4-fluorobenzoic acid [((5-nitro)thiophen-2yl) methylene]hydrazide showed the highest inhibitory activity in this series. The search of pharmacophores was done by means of the Electronic-Topological Method (ETM). The model developed in this study is supposed to be applied to the design, preparation and screening of new compounds of similar structure in order to further test and optimize the model with the eventual goal of preparing new anti-tubercular agents. (c) 2006 Elsevier Masson SAS. All rights reserved.
Keywords: antituberculosis activity; hydrazide-hydrazones; structure-activity relationships; ANTIMYCOBACTERIAL ACTIVITY; ANTICONVULSANT ACTIVITY; ANTIMICROBIAL ACTIVITY; ANTIFUNGAL ACTIVITY; MIXED SERIES; ODOR; ACID; DERIVATIVES